2013
DOI: 10.1021/es400676q
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Pure N2O to Biochars and Other Organic and Inorganic Materials under Anhydrous Conditions

Abstract: Suppression of nitrous oxide (N2O) emissions from soil is commonly observed after amendment with biochar. The mechanisms accounting for this suppression are not yet understood. One possible contributing mechanism is N2O sorption to biochar. The sorption of N2O and carbon dioxide (CO2) to four biochars was measured in an anhydrous system with pure N2O. The biochar data were compared to those for two activated carbons and other components potentially present in soils-uncharred pine wood and peat-and five inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 47 publications
5
72
0
Order By: Relevance
“…The CO 2 adsorption capacity of the biochar presented in this study was very close to that reported in the literature [59]. However, it should be noted that the biochar in the literature was prepared by a two-stage slow pyrolysis process (1e5 min exposure to 700 C followed by a 10e60 min exposure to 200À500 C) [59], and the biochar in this study was prepared at approximately 300 C for 20 min only.…”
Section: Prospects Of Biochar As a Co 2 Adsorbentsupporting
confidence: 83%
See 1 more Smart Citation
“…The CO 2 adsorption capacity of the biochar presented in this study was very close to that reported in the literature [59]. However, it should be noted that the biochar in the literature was prepared by a two-stage slow pyrolysis process (1e5 min exposure to 700 C followed by a 10e60 min exposure to 200À500 C) [59], and the biochar in this study was prepared at approximately 300 C for 20 min only.…”
Section: Prospects Of Biochar As a Co 2 Adsorbentsupporting
confidence: 83%
“…However, it should be noted that the biochar in the literature was prepared by a two-stage slow pyrolysis process (1e5 min exposure to 700 C followed by a 10e60 min exposure to 200À500 C) [59], and the biochar in this study was prepared at approximately 300 C for 20 min only. Besides, there was another biochar whose CO 2 adsorption capacity was lower than that of present study, and it was produced by carbonization at 600 C [60].…”
Section: Prospects Of Biochar As a Co 2 Adsorbentmentioning
confidence: 99%
“…Although the ways to decrease nitrification N 2 O have not been well characterized, it has been shown that the decreases of soil N 2 O emissions were often accompanied by lower nitrification rates. 16 Several hypotheses have been proposed for N 2 O decreases by biochar, including: (i) biochar reduces levels of denitrification via improving soil aeration; 17 (ii) biochar increases the adsorption of NO 3 − , thus decreasing substrate availability for denitrification; 18 (iii) biochar increases soil pH therefore driving denitrification thorough to N 2 ; 18 (iv) biochar sorbs N 2 O; 19 and (v) biochar contains ethylene which could inhibit nitrification and thus the formation of NO 3 − and N 2 O. 20 More studies are needed to clarify the effect of biochar, especially when it is used as a soil amendment in agricultural production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…by a pH increase) leading to a decreased N 2 O/(N 2 O + N 2 ) emission ratio11151640, or (iii) the contribution of abiotic processes such as sorption of N 2 O onto biochar particles and abiotic reduction of N 2 O to N 2 by redox active compounds4142. However, systematic studies focusing on the underlying geochemical and microbial processes causing N 2 O emission mitigation are rare and the contributing mechanisms are not fully understood yet.…”
mentioning
confidence: 99%